RESPON ORGANISASI ISLAM TRANSNASIONAL DI INDONESIA TERHADAP PROGRAM DERADIKALISASI BADAN NASIONAL PENANGGULANGAN TERORISME (BNPT) - Hermastuti, Mirza Dwiky; Windiani, Reni; Wahyudi, Fendy Eko (Journal of International Relations, 2016)
The issue of terrorism is increasingly become world's attention post 11September 2001. One of the handling of the crime of terrorism is through thesoft approach conducted with de-radicalization program. Indonesia's deradicalizationprogram conducted by BNPT obtained objections fromTransnational Islamic Organizations in Indonesia. This research aims to findout the factors that influence the Transnational Islamic Organization’sresistance towards de-radicalization program of BNPT viewed from socialmovements perspective. The research method is qualitative and the type ofresearch is explanatory that explain the cause of rejections from TransnationalIslamic Organizations towards the de-radicalization program BNPT. Thisresearch uses globalization theory by Holton and social movements theory byMcCarthy and Zald. The results of this research indicate that the rejection’sresponse to the de-radicalization BNPT is a form of backlash conscious byTransnational Islamic Organizations to oppose Western thought. Viewed fromthe perspective of social movements, framing, and resource mobilizationstrategies seen in the rejection’s movements of the Transnational IslamicOrganization. In addition the political opportunity structure in the reformationera makes the system and political structure existed became more open. It hasprovided an opportunity for Transnational Islamic Organization to conduct itsmovement in criticizing the government.